Calibrating the microscopic properties of quartz sand with coupled CFD-DEM framework. Issue 4 (13th June 2016) - Derakhshani, Sayed M.; Schott, Dingena L.; Lodewijks, Gabriel
Abstract : Purpose: – The macroscopic properties of dried sand can be correctly modelled when the accurate determination of the microscopic properties is available. The microscopic properties between the particles such as the coefficients of rolling ( µ r ) and sliding ( µ s ), are numerically determined in two different ways: with and without considering the fluid effect. In an earlier study, the microscopic properties were determined by discrete element method (DEM) and without considering the air effect on the macroscopic properties such as the Angle of Repose. The purpose of this paper is to recalibrate the microscopic properties through a coupling between the DEM and computational fluid dynamics (CFD). Design/methodology/approach: – The first step is dedicated to the calibration of the CFD-DEM model through modelling a single particle sedimentation within air, water, and silicon oil. The voidage and drag models, the grid size ratio (D/dx), the domain size ratio (W/D), and the optimum coupling interval between the CFD and DEM were investigated through comparing the CFD-DEM results with the analytical solution and experimental data. The next step is about modelling an Hourglass with the calibrated CFD-DEM model to recalibrate the µ r and µ s of dried sand particles. Findings: – It was concluded that the air has a minor effect on the macroscopic properties of the dried sand and the µ r and µ s that were obtained with the DEM can be utilized in the CFD-DEM simulation. Originality/value: – Utilizing the granulometry of dried quartz sand in the calibration process of the CFD-DEM method has raised the possibility of using the µ r and µ s for other applications in future studies.